KOMPETENSI PPL DAN KEMAMPUAN KELOMPOK TANI DALAM MENUNJANG BP3K BERPRESTASI DI KECAMATAN RAMAN UTARA KABUPATEN LAMPUNG TIMUR - Yohilda Elva Putri; Dewangga Nikmatullah; Begem Viantimala (Lampung University, 2019)
The research is to analyze competence of Agricultural Extension Workers (AEWs), ability of farmer groups, and analyze relationship between the AEWs’ competence and the ability of farmer groups to support the distinguished North Raman BP3K. The research method used is a survey carried out in North Raman subdistrict of East Lampung. Data were collected in March - July 2017. The data are analyzed descriptively and using Kruskals Wallis test. Respondents are 77 people consisting of three AEWs’ and 74 rice farmers in North Raman subdistrict specified using a purposive sampling method. The results showed the Competence of the AEWs’ is in medium category and the ability of farmer groups is in medium category. There is relationship between the competence of the AEW’s and the ability of farmer groups to support the distinguished BP3K in North Raman subdistrict.Key words: AEWs’ Competence, BP3K, farmer groups’ capability